2021
DOI: 10.3390/ijms222111928
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin 1B Gene Plays an Important Role in Loach Barbel Air-Breathing

Abstract: Loach (Misgurnus anguillicaudatus) is well known to perform air-breathing through the posterior intestine and skin. However, we find here for the first time a unique central vascular structure in the loach barbel, with a blood–gas diffusion distance as short as that of the posterior intestine. Under acute hypoxia, the distance of loach barbels became significantly shorter. Moreover, barbel removal significantly decreased air-breathing frequency of the loach. These findings imply that the barbel is another air-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Oxygen is vital for the survival of most life forms. With various ABOs, M. anguillicaudatus markedly enhances its hypoxic tolerance to the bottom mud, providing a good model for studying the evolution of benthic adaptability in the accessory respiratory organs (Sun et al 2021;Huang et al 2022;Huang et al 2021). Here, we found that oxygen transport-related GO categories (oxygen binding (GO:0019825, P = 3.11E-12), gas transport (GO:0015669, P = 1.48E-12), oxygen transport (GO:0015671, P = 1.48E-12) and hemoglobin complex (GO:0005833, P = 2.86E-13)) significantly expanded in the loach genome ( Table S2-(3)).…”
Section: Air-breathing and Evolution Of Loach Intestinementioning
confidence: 99%
See 3 more Smart Citations
“…Oxygen is vital for the survival of most life forms. With various ABOs, M. anguillicaudatus markedly enhances its hypoxic tolerance to the bottom mud, providing a good model for studying the evolution of benthic adaptability in the accessory respiratory organs (Sun et al 2021;Huang et al 2022;Huang et al 2021). Here, we found that oxygen transport-related GO categories (oxygen binding (GO:0019825, P = 3.11E-12), gas transport (GO:0015669, P = 1.48E-12), oxygen transport (GO:0015671, P = 1.48E-12) and hemoglobin complex (GO:0005833, P = 2.86E-13)) significantly expanded in the loach genome ( Table S2-(3)).…”
Section: Air-breathing and Evolution Of Loach Intestinementioning
confidence: 99%
“…To better identify air-breathing-related genes of the loach, on the basis of our previous studies including developmental transcriptome analysis of loach posterior intestines , intestinal air-breathing inhibition trial (transcriptome ) and microRNAs ) analysis), comparative transcriptome analysis of posterior intestines between the loach and non-air-breathing L. elongata (Huang et al 2022), an air exposure trial (namely, an intestinal air-breathing enhancement trial) was performed and the procedures in details were described as Sun et al (Sun et al 2021). A total of 18 WT loaches were used for transcriptome analysis.…”
Section: Identification Of Air-breathing-related Genes Of the Loachmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, some fish species, such as M. anguillicaudatus , Ophiocephalus argus , and Protopterus annectens , have evolved accessory air-breathing organs (ABOs) to adapt to anoxic environments [ 9 11 ]. Specifically, M. anguillicaudatus uses multiple ABOs including posterior intestine, skin, and barbel, to do air-breathing to maintain their blood oxygen saturation [ 12 ]. M. anguillicaudatus has become an appropriate model for investigating the evolution of benthic adaptability in the ABOs [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%